THE EFFECT OF COMPETENCE AND WORK DISCIPLINE ON REWARDS WITH WORK INFRASTRUCTURE AS A MODERATING VARIABLE AT PT PLN (PERSERO) SERVICE IMPLEMENTATION UNIT RANTAUPRAPAT CUSTOMERS - Hendra Gunawan Nainggolan; Kiki Farida Ferine (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the influence of Competence and Work Discipline on Rewards with Work Infrastructure as a moderating variable at PT PLN (Persero) Rantauprapat Customer Service Implementation Unit. This study uses a quantitative approach with the Partial Least Square Structural Equation Modeling (PLS-SEM) analysis method. The number of respondents in this study was 86 people. The results showed that Competence (coefficient = 0.388; T-statistic = 3.266; P-values ​​= 0.001) and Work Discipline (coefficient = 0.276; T-statistic = 2.307; P-values ​​= 0.011) had a positive and significant effect on Rewards. Work Infrastructure also had a positive and significant effect on Rewards (coefficient = 0.362; T-statistic = 3.274; P-values ​​= 0.001). However, the moderation effect test shows that the interaction between Competence and Work Infrastructure (coefficient = -0.031; T-statistic = 0.235; P-values ​​= 0.407), as well as the interaction between Work Discipline and Work Infrastructure (coefficient = 0.112; T-statistic = 0.900; P-values ​​= 0.184), do not significantly influence Rewards. Thus, employee Rewards are more directly influenced by competence, discipline, and the availability of work infrastructure, compared to the moderating effect of work infrastructure.